Research Workshop for Students in the Center of Japanese Studies, University of Indonesia: A Community Service Activity - Abdurrahman, M Kamil Ghiffary (Jurnal Pengabdian Masyarakat Bangsa, 2024)
This article believes that university students should possess a higher level of critical thinking skills after they graduate, which can also be evaluated from their thesis writing project. The capacity to formulate a logical research problem based on empirical observation and academic evaluation is the indicator we are trying to have, thus, assess. This assessment is not the only agenda we are having in this community service activity; we also try to improve and elevate students' capacity of understanding how research works by providing further mentorship consisting of brainstorming and discussion sessions to ignite their critical thinking capacity. Nevertheless, this activity has a guiding question whether university students are able to critically identify and formulate research questions for their thesis writing project. By accepting and archiving their ideas and research proposals, we have found three important findings. First, the students are still struggling to start and set up their research proposals since many of their empirical observations are based on the subjective perception of reality, inspired from self-centered activities like hobbies and subjective preferences. Second, these subjective interpretations manifest into the low awareness of the existing previous literature for their own research, hence, making their research topic to be far from possessing an urgency of writing both empirically and academically. Third, it was also imperative that most of the students are not fully aware of the options of theoretical and conceptual framework they will use as the analytical lenses, left alone its definitions, its applications, and its debates.